2020
DOI: 10.1242/dev.183665
|View full text |Cite
|
Sign up to set email alerts
|

Notch signalling regulates epibranchial placode patterning and segregation

Abstract: Epibranchial placodes are the geniculate, petrosal and nodose placodes that generate parts of cranial nerves VII, IX and X, respectively. How the three spatially separated placodes are derived from the common posterior placodal area is poorly understood. Here, we reveal that the broad posterior placode area is first patterned into a Vgll2 + /Irx5 + rostral domain and a Sox2 + /Fgf3 + / Etv5 + caudal domain relative to the first pharyngeal cleft. This initial rostral and caudal patterning is then sequentially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…We have previously demonstrated that in the developing PAs, the proximal pharyngeal epithelium was derived from the posterior placodal area and overlap with the epibranchial placodal cells ( Figure 1I , red dotted line; Zhang et al, 2017 ; Wang et al, 2020 ), while the distal PAs were enveloped by pharyngeal ectodermal epithelium. Therefore, the proximal and distal pharyngeal epithelium were composed of developmentally distinct epithelial cells.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…We have previously demonstrated that in the developing PAs, the proximal pharyngeal epithelium was derived from the posterior placodal area and overlap with the epibranchial placodal cells ( Figure 1I , red dotted line; Zhang et al, 2017 ; Wang et al, 2020 ), while the distal PAs were enveloped by pharyngeal ectodermal epithelium. Therefore, the proximal and distal pharyngeal epithelium were composed of developmentally distinct epithelial cells.…”
Section: Resultsmentioning
confidence: 87%
“…As Notch signaling has been shown to be critical for the development of epibranchial placodal epithelium and proximal PAs ( Zhang et al, 2017 ; Wang et al, 2020 ), we examined Jag1 which was expressed in the proximal pharyngeal epithelium of developing PAs and restricted to the pharyngeal clefts and pouches as the segmental plates were formed at E9.5 ( Figures 2G,I,K ). Interestingly, we found that the expression of Jag1 was ectopically activated in the entire pharyngeal ectodermal region of PA2 and posterior PA1 in the Hoxb3 Tg/+ mutants at E9.5 ( Figures 2H,J ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations